1996
DOI: 10.1104/pp.112.3.1383
|View full text |Cite
|
Sign up to set email alerts
|

3,7-Dichloroquinolinecarboxylic Acid Inhibits Cell-Wall Biosynthesis in Maize Roots

Abstract: The mode of action of the herbicide 3,7-dichloroquinolinecar-boxylic acid (quinclorac) was examined by measuring incorporation of [14C]glucose, [14C]acetate, [3H]thymidine, and [3H]uridine into maize (Zea mays) root cell walls, fatty acids, DNA, and RNA, respectively. Among the precursors examined, 10 [mu]M quinclorac inhibited [14C]glucose incorporation into the cell wall within 3 h. Fatty acid and DNA biosynthesis were subsequently inhibited, whereas RNA biosynthesis was unaffected. In contrast to the cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…When quinclorac was applied to Zea mays and Digitaria ischaemum, it inhibited their growth, changed the flow of electrons on young tissues and caused the tissue necrosis on the elongation zone of these monocots (Koo et al, 1994). Due to these symptoms and to other physiological responses, it was stated that Integrative theory of the mode of action of quinclorac: literature review these responses would be associated to the inhibition of the cellular expansion (Koo et al, 1996). Similar effects are found in other herbicides that inhibit cell wall synthesis, such as oxaziclomefone (O'Looney & Fry, 2005) and diclobenil (Peng et al, 2001;DeBolt et al, 2007;Wightman & Turner, 2010).…”
Section: Effect On the Formation Of The Cellular Wallmentioning
confidence: 87%
See 3 more Smart Citations
“…When quinclorac was applied to Zea mays and Digitaria ischaemum, it inhibited their growth, changed the flow of electrons on young tissues and caused the tissue necrosis on the elongation zone of these monocots (Koo et al, 1994). Due to these symptoms and to other physiological responses, it was stated that Integrative theory of the mode of action of quinclorac: literature review these responses would be associated to the inhibition of the cellular expansion (Koo et al, 1996). Similar effects are found in other herbicides that inhibit cell wall synthesis, such as oxaziclomefone (O'Looney & Fry, 2005) and diclobenil (Peng et al, 2001;DeBolt et al, 2007;Wightman & Turner, 2010).…”
Section: Effect On the Formation Of The Cellular Wallmentioning
confidence: 87%
“…According to the physiology of the plant species (as described) and the concentration of quinclorac, the biosynthesis of the cellular wall may be inhibited (Koo et al, 1996). Three hours after the application of quinclorac on corn, it was observed that GAX and cellulose were notably inhibited, while MG was inhibited five hours after spraying (Koo et al, 1996).…”
Section: Effect On the Formation Of The Cellular Wallmentioning
confidence: 99%
See 2 more Smart Citations
“…It was previously reported that quinclorac inhibits the incorporation of glucose into cellulose in a dose and time-dependent manner (Koo et al, 1996(Koo et al, , 1997, being regarded as a cellulose biosynthesis inhibitor (CBI) (Vaughn, 2002). However, other works challenged the correlation of cellulose inhibition effect and quinclorac mechanism of action (Tresch and Grossmann, 2003).…”
Section: Introductionmentioning
confidence: 99%